The Role of Tahura Sultan Adam's Existence in Supporting the Economy of the Surrounding Community - Rusmaniah, Rusmaniah; Mutiani, Mutiani; Jumriani, Jumriani; Sari, Raihanah; Triyono, Sigit; Firdaus, Ahmad Maulana (Journal of Social Development, 2024)
The Grand Forest Park (Tahura) is essentially built and developed as regional wealth. For the sake of economic development and conservation towards Law Number 22 of 1999 concerning regional government and Law number 41 of 99 concerning forestry, Tahura has an important role for local governments to develop the development of the Tahura area. Is expected to have an important role in the development of economic activities and regional conservation activities as tourism education research activities for community development around the area and biodiversity conservation. In the Tahura study, Sultan Adam was chosen as the object of research or object of study, considering that he is located in Mandiangin Village, Banjar Regency, under the auspices of the South Kalimantan Provincial Forestry Service. The purpose of this research was to see how the role of Tahura has on the economic development of the surrounding community. The research method used in this study is a survey method. The presence of visitors does not always have an impact on the sales results obtained by traders. Sometimes visitors have brought their own food. Visitors who come from certain communities and agencies who carry out activities at the Sultan Adam Tahura often bring their own food ordered from other places. This is because there is an assumption that the prices of goods at tourist sites are more expensive, so visitors choose to bring their own food from home.